SAT0464 MULTIPLE REBOUND-ASSOCIATED VERTEBRAL FRACTURES AFTER DENOSUMAB DISCONTINUATION IN RHEUMATOLOGY CLINIC. (2nd June 2020) - Evangelatos, G.; Fragoulis, G. E.; Iliopoulos, A.
Abstract : Background: Denosumab, a monoclonal antibody against RANKL, is an effective treatment for osteoporosis. Discontinuation of denosumab has been shown to lead in multiple vertebral fractures in some patients due to a severe acceleration of bone resorption (rebound-associated vertebral fractures-RAVFs). Limited data published during the last 2 years highlighted this issue. Objectives: The aim of this case series is to describe features of the denosumab-associated RAVFs and the characteristics of these patients. Methods: Patients from our outpatient rheumatology clinic who were diagnosed with recent vertebral fractures after denosumab discontinuation from January 2019 to December 2019 were included. Diagnosis was based on x-ray and/or magnetic resonance imaging (MRI) of thoracic (T) or lumbar (L) spine. All cases were the result of reduced compliance of the patients to the treatment regimen. A baseline x-ray examination was available in all patients included and was compared in order to exclude prevalent osteoporotic fractures. Demographic and clinical parameters were recorded. Results: Nine patients (8 females) with a mean±SD age of 71.3±11.9 years were included (Table 1 ). A total of 32 fractures occurred, affecting median 4 (range 1-6) vertebras (Figure 1 ). The mean±SD duration of denosumab treatment prior to discontinuation was 54.0±30.1 months, while the mean±SD time that RAVFs occurred after the last denosumab injection was 8.8±2.4 (range 7-12) months. The most commonly affected vertebra was L3 (Table1). Most patients (66.7%) did not have any prevalent osteoporotic fracture. Four patients (44.4%) were receiving drugs that affected bone metabolism (mainly corticosteroids and aromatase inhibitors). Only 33.3% of the patients had a history of previous treatment with bisphosphonates. Conclusion: Denosumab-associated RAVFs usually occur within 7-12 months after the last denosumab injection and affect multiple vertebras. Most cases are associated with long-term (>2 years) denosumab administration without previous treatment with bisphosphonates. Rheumatologists should be alert of this complication since the reported compliance in patients under denosumab treatment is only 46% (1) and the expected incidence of RAVFs after denosumab discontinuation has been reported to be 10% (2). References: [1]Durden E, Pinto L, Lopez-Gonzalez L, Juneau P, Barron R. Two-year persistence and compliance with osteoporosis therapies among postmenopausal women in a commercially insured population in the United States. Arch Osteoporos. 2017 Dec;12(1):22. [2]McClung MR, Wagman RB, Miller PD, Wang A, Lewiecki EM. Observations following discontinuation of long-term denosumab therapy. Osteoporos Int. 2017 May;28(5):1723-1732. Disclosure of Interests: None declared